Using multiple URIResolvers for the same stylesheet added flexibility opens new opportunities. - Tolle, Troy
A URIResolver, an interface defined in the javax.xml.transform package, is used to process a URI and create a Source object out of it. All Java developers working with XSLT have to decide which URIResolver they're going to use to resolve the URL.